1988
DOI: 10.1007/bf00278750
|View full text |Cite
|
Sign up to set email alerts
|

Insulin autoantibody polymorphisms with greater discrimination for diabetes in humans

Abstract: Summary.Insulin autoantibodies, like islet cell antibodies, are found not only in the sera of newly diagnosed Type 1 (insulin-dependent) diabetic patients and their relatives, but also in patients with other autoimmunities who do not develop diabetes. Insulin autoantibodies are oligo/monoclonal and frequently binding-site restricted. As determinant selection is genetically determined, we questioned whether certain polymorphisms of insulin autoantibodies, identified by their binding site on the insulin molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Neither GAD nor insulin have been identified by the library screening approach. Diabetes-associated antibodies to these antigens are known to bind epitopes that are highly dependent on protein conformation (26,27), and these may not be displayed by the library. If the 40,000-M, fragments of islet antigen are indeed equivalent to IA-2 and ICA512, then this protein will represent a rare case of an islet antigen identified by both immunochemical and molecular biological approaches.…”
Section: Resultsmentioning
confidence: 99%
“…Neither GAD nor insulin have been identified by the library screening approach. Diabetes-associated antibodies to these antigens are known to bind epitopes that are highly dependent on protein conformation (26,27), and these may not be displayed by the library. If the 40,000-M, fragments of islet antigen are indeed equivalent to IA-2 and ICA512, then this protein will represent a rare case of an islet antigen identified by both immunochemical and molecular biological approaches.…”
Section: Resultsmentioning
confidence: 99%
“…These were not the same as the polyreactive antibodies previously described, since, unlike the polyreactive antibodies, they could not be inhibited by excess tetanus toxoid or single-stranded DNA (data not shown). IAAs with distinct binding characteristics (16), proinsulin autoantibodies (17), and high-titer, low-affinity IAAs in subjects with the rare insulin autoimmune hypoglycemia (18, 19) have also been described. The findings of this study are relevant to both pathogenesis and prediction of T1DM.…”
Section: Discussionmentioning
confidence: 99%
“…However, the dynamics and diversity of the autoimmune repertoire can already be demonstrated in subjects with a lone islet-cell autoantibody [145,148,150]. For example, binding studies of IAA-positive sera with insulin variants have shown epitope restriction, allowing the differentiation of diabetes-related IAA from diabetes-unrelated IAA [83]. Another recent study showed that the autoimmune response to GAD in children is initially directed against the middle region of GAD, while later spreading mostly to the NH 2 -terminal epitope [150].…”
Section: Insulinmentioning
confidence: 98%